“Homework Online” as an Innovative Technology of Teaching a Foreign Language - Islomovna, Kamalova Aziza (European Journal of Life Safety and Stability (2660-9630), 2021)
the article raises the problem of reducing the performance of homework in a foreign language, as one of the main ways to consolidate the material obtained in a practical lesson, control and self-control. With the help of an Internet service Learningapps.org the author suggests an experiment on the topic “Homework online” with a group of students; which contributed to the popularization of homework among pupils, increased the percentage of knowledge quality and developed the skill of working with information.